THE TEACHERS’ VOICES: UNDERSTANDING AND DEVELOPING STUDENTS’ TALENTS - Wahidah; Teuku Zulfikar; Zahratul Idami; Fadhilah Wiandari; Cherry Julida Panjaitan (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This article analyzes teachers' perspectives on talents and talent development of high school students in Langsa City. Using a qualitative approach, researchers collected data from three high schools, namely Vocational High School 2, State High School 1, and Madrasah Aliyah Negeri 2 Langsa through interview techniques with student affairs teachers. The research results show that the introduction and development of talents in senior high schools in Langsa includes: socialization at the beginning of the new school year, mentoring, development in various extracurricular activities and tentative talent development. Talent development through extracurricular activities focuses on talents that comes from five senses, while talents that come from nature tends to be neglected. The implications of the results of this research are that schools need to develop talent development activities that are integrated with the co[1]curriculum so that they can accommodate all students' talents.